Implementasi Peran dan Tugas Guru Pembimbing Khusus (GPK) pada Pendidikan Inklusi di Sekolah Dasar Negeri - Pujiastuti, Arik Umi; Agustin, Ina (Penerbit STKIP PGRI Bangkalan, 2019)
Ina Agustin, Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas PGRI Ronggolawe Tuban inaagustin88@gmail.com Arik Umi Pujiastuti Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas PGRI Ronggolawe Tuban arik.umi 86@gmail.com Abstract The objectives of this study are: 1) to describe the implementation of the Special Advisory Teacher (GPK) roles and duties on inclusive education of all of state Elementary Schools in Soko, Tuban on process of identifying types of needs, assessment, and compiling individual learning programs, 2) to describe the implementation of GPK roles and duties related to the designing process and giving specific programs, and 3) to describe the implementation of GPK roles and duties in modifying teaching materials. The research method is qualitative descriptive. The data collection instruments used are interviews and field notes. The results of this study are, 1) the role and duties of Special Advisory Teacher (GPK) at inclusive education on  the process of identifying needs, assessment, and compiling individual teaching programs that run less than optimal because the lack of resources, 2) in the designing process and giving specific programs that must be carried out by Special Advisory Teacher (GPK) does not run optimally due to differences in perceptions between GPK in giving specific programs to the needs of ABK, 3) in the implementation of GPK role in modifying teaching materials , actually it hasn’t run well. It because the lack of resources and funds sources. Based on the results of the study, the implementation of GPK roles and duties in identifying types of needs, assessment, preparation of individual learning programs, designing learning, giving specific programs, and modifying teaching materials were not optimal. As for the lack of optimal implementation of GPK roles and duties due to lack of resources (GPK), lack of socialization regarding the roles and duties of GPK, and regulations related to main duty ann functions from GPK.  Key words: GPK roles and duties, inclusive education   Abstrak Tujuan dari penelitian ini adalah: 1) mendeskripsikan implementasi dari peran dan tugas guru pembimbing khusus(GPK) pada pendidikan inklusi di Sekolah Dasar Negeri se- Kecamatan Soko Kabupaten Tuban dalam proses identifikasi jenis kebutuhan, assesment, dan menyusun program pembelajaran individual, 2) mendeskripsikan implementasi peran dan tugas GPK terkait dengan proses perancangan dan pemberian program khusus, dan 3) mendeskripsikan implementasi peran dan tugas GPK dalam memodifikasi bahan ajar. Adapun metode penelitian ini adalah, deskriptif kualitatif. Instrumen pengumpulan data yang digunakan adalah, wawancara dan catatan lapangan. Hasil dari penelitian ini adalah,1) peran dan tugas guru pembimbing khusus(GPK) pada pendidikan inklusi di dalam proses identifikasi kebutuhan, assesment, dan menyusun program pembelajaran individual berjalan kurang optimal penyebabnya, adanya kekurangan jumlah sumber daya, 2) pada proses perancangan dan pemberian program khusus yang harus dilaksanakan Guru Pembimbing Khusus (GPK) tidak berjalan dengan optimal dikarenakan perbedaan persepsi antar GPK dalam pemberian program yang spesifik sesuai dengan kebutuhan ABK, 3) pada inplementasi peran GPK terkait memodifikasi bahan ajar pada kenyataannya belum bisa terlaksana dengan baik penyebabnya, kurangnya sumber daya dan sumberdana. Berdasarkan hasil penelitian maka implementasi peran dan tugas GPK dalam identifikasi jenis kebutuhan, assesmen, penyusunan program pembelajaran individual, merancang pembelajaran, pemberian program yang spesifik, dan memodifikasi bahan ajar kurang berjalan dengan optimal. Adapun adanya kurang optimal dari implementasi peran dan tugas GPK disebabkan karena, kurangnya sumber daya (GPK), kurangnya sosialisasi terkait peran dan tugas dari GPK, dan peraturan terkait tupoksi dari GPK   Kata Kunci: Peran dan tugas GPK, pendidikan inklusi